A cognitive poetics of kinaesthesia in Wordsworth - Yuan, Wenjuan (2013)
This project is an effort to explore the kinetic aspects of Wordsworth's works on the one hand and scale up cognitive grammar (Langacker, 2008; Talmy, 2000a, 2000b) to literary discourse on the other hand, both of which stand as relatively underdeveloped areas in a cognitive approach to literature. Specifically, I focus on the kinetic and kinaesthetic notions of motion, force and energy expounded in cognitive grammar, mainly, fictive motion, force dynamics and energy chains, addressing issues not only related to kinetic representation in literary texts but also its possible effects upon readers. With the English Romantic poet Wordsworth as the case study, I conduct detailed cognitive poetic analyses of selected poems, mainly informed by some cognitive grammatical constructs, to reveal the 'invisible' meaning of the text (Langacker, 1993).